2004
DOI: 10.1002/prot.20006
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein in the primary step of the photoreaction of yellow protein

Abstract: We show the unexpectedly important role of the protein environment in the primary step of the photoreaction of the yellow protein after light illumination. The driving force of the trans-to-cis isomerization reaction was analyzed by a computational method. The force was separated into two different components: the term due to the protein-chromophore interaction and the intrinsic term of the chromophore itself. As a result, we found that the contribution from the interaction term was much greater than that comi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
(37 reference statements)
1
32
0
Order By: Relevance
“…In a very recent report (30), the gas-phase absorption spectrum of the PYP chromophore indicates that the excitation energy is lower than calculated value (22), indicating that an excess vibrational energy is sufficient for double-bond twisting. Moreover, recent molecular dynamics calculations for the protein and in vacuo support the involvement of the double-bond twisting (31). The protein environment is not significant in changing the lowenergy barrier for twisting, but it is critical for the subsequent conversion to the cis form and for the impedance of radical formation during the cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In a very recent report (30), the gas-phase absorption spectrum of the PYP chromophore indicates that the excitation energy is lower than calculated value (22), indicating that an excess vibrational energy is sufficient for double-bond twisting. Moreover, recent molecular dynamics calculations for the protein and in vacuo support the involvement of the double-bond twisting (31). The protein environment is not significant in changing the lowenergy barrier for twisting, but it is critical for the subsequent conversion to the cis form and for the impedance of radical formation during the cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Some of us showed that as long as there is a core part, ONIOM can even partition the chromophore into different regions. 18,22 Whereas the behavior of ONIOM for ground state energies has been investigated in numerous works, there are only few reports in the literature on the calculation of transition energies, [22][23][24][25][26][27][28][29][30][31][32][33][34] of which several used QM/QM combinations. The goal of this work is to investigate further the effectiveness of ONIOM͑QM:QM͒ for the description of excited states.…”
Section: Introductionmentioning
confidence: 99%
“…In PYP the asymmetric protein−chromophore interaction probably serves as the initial accelerant for the light induced photocycle,(50) which ultimately leads to a cis−trans isomerization. (51)…”
Section: Introductionmentioning
confidence: 99%